The Oneness of God behind the Local Tradition of Nusantara Islam: Theo-Anthropological Perspective with Interpretive Paradigm on Nusantara Islam Sasak Lombok - Mohamad Iwan Fitriani (Ulumuna, 2015)
This study aims to elucidate Nusantara Islam and finds the concept of oneness of God within the Sasak Muslim traditions as analytical tool to understand Nusantara Islam in the local context of Lombok. God is only one, but ways of finding “The One” vary. Islamic teachings manifest in local traditions are termed Nusantara Islam. In this study, Nusantara Islam is analyzed theoretically and practically regarding Sasak Muslim traditions. This study uses a qualitative approach and employs the interpretive paradigm and Theo-anthropological perspective. This study shows that Nusantara Islam in Lombok can be observed through various religious concepts, practices and rituals, such as mulut (the celebration of Prophet’s birthday), maleman (last ten days of fasting Ramadan month) and rowah (sending prayer to the dead). Tawḥīd or the notion of One God lies behind these traditions. Tawḥīd is more than just the notion of oneness of God; it is a worldview manifesting not only in spiritual domains but also in socio-cultural spheres. DOI: http://dx.doi.org/10.20414/ujis.v19i2.334